The Influence of Attitude, Subjective Norms, Perceived Behavioral Control, Environmental Concern and Environmental Awareness on the Purchase Intention of Palm Cooking Oil in Medan City - Meutia, Anna; Wibowo, Rulianda Purnomo; Rahmanta, Rahmanta (West Science Agro, 2025)
The growth of environmental awareness and sustainable consumer behavior has become an important issue in recent years. In the city of Medan, as one of the major cities in Indonesia, cooking oil consumption is an integral part of people's daily lives. However, the production and use of cooking oil also has a significant impact on the environment. This study aims to find out how consumer behavior towards the intention to buy environmentally friendly palm cooking oil. The analysis method used is Partial Least Square – Structural Equation Modelling (PLS-SEM) using the SmartPLS version 4 application and sampling technique by means of judgement sampling or purposive sampling consisting of 100 respondents. The results of this study show that Environmental Awareness is the most significant influence on the purchase intention of housewives in environmentally friendly palm cooking oil products. Furthermore, it was followed by Perception Behavior Control and Subjective Norms which had a positive and significant effect on the Purchase Intention of environmentally friendly palm cooking oil. Meanwhile, Attitude and Environmental Concern did not have a significant effect on the Purchase Intention of palm cooking oil in Medan City.